Legitimasi Penetapan Status Negeri Di Kecamatan Teon, Nila, Serua, Kabupaten Maluku Tengah Sebagai Desa Adat - Lelapary, Elfira; Bakarbessy, Andress Deny; Pattinasarany, Yohanes (Jurnal Saniri, 2024)
Even though it is recognized, the legitimacy of traditional village status is often a problem. The determination of countries as traditional villages without traditional territories or petuanan is as regulated in Article 97 of Law Number 6 of 2014 concerning Villages, that one of the requirements for establishing a traditional village is that the customary law community unit must have a territory or customary area. However, the regional government of Central Maluku Regency has designated the Negeris in the TNS sub-district as traditional villages but do not have territory or customary areas. There are two problem formulations that will be discussed in this paper, namely whether the determination of the status of the lands in Teon, Nila, Serua sub-districts, Central Maluku district has legitimacy as traditional villages without having customary territories?, and what are the legal consequences if the status of the lands in Teon, Nila, Serua sub-districts, Central Maluku district has legitimacy as a traditional village without having a traditional territory     Normative research was conducted to analyze the application of positive legal norms in traditional village legitimacy policies. The government's decision to legitimize the status of traditional villages is crucial to respecting the recognition and maintaining the identity of traditional villages, in accordance with existing norms.     The results of this research are that the determination of State status in Teon, Nila, Serua Districts, Central Maluku Regency does not have legitimacy so the result is null and void.